Preserving the Earth as Maqashid al-Shariah: A Maqashidi Interpretation of Qur’anic Verses Prohibiting Environmental Corruption - Syafira Mujahidah Charis; M. Sihabudin (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research examines the Qur’anic verses prohibiting acts of destruction on earth using a maqashidi exegetical approach, integrating them into the five aspects of daruriyyat al-khamsah (religion, life, intellect, lineage, and property). Employing a qualitative library-based research method with a thematic (maudhu’i) approach, this study analyzes QS. Al-Baqarah [2]: 11, QS. Al-Baqarah [2]: 205, QS. Al-A’raf [7]: 56, and QS. Ar-Rum [30]: 41, with reference to four contemporary commentaries: Tafsir al-Maraghi, Tafsir al-Jawahir, Tafsir al-Misbah, and Tafsir al-Azhar. The findings demonstrate that the prohibition against causing damage on earth constitutes an integral part of the objectives of Islamic law (maqashid al-syariah). Furthermore, this research offers a critical analysis of the limitations of classical exegesis in addressing contemporary ecological issues and proposes hifz al-bi’ah (environmental preservation) as a solution to environmental degradation.    The results show that the prohibition against causing damage on earth is not merely an ecological moral imperative but an integral part of the objectives of sharia. These four verses implicitly contain the protection of all five maqashid simultaneously. Thus, environmental preservation from a maqashid perspective is an obligation equivalent to protecting religion, soul, intellect, lineage, and property.